A Morphological Process of Derivational Affixes in Popular LINE Webtoon: The Annarasumanara - Nisa, Baiatun (REiLA : Journal of Research and Innovation in Language, 2020)
This research tries to analyze the morphological process of derivational affixes in a popular LINE Webtoon comic titled Annarasumanara authored by Il Kwon Ha. This research uses a synchronic descriptive approach in which data are collected and explained naturally. The objects of this research are the conversations in Annarasumanara from episode 1 to 10. The results of the research are 53 words that changed word classes, involving 7 derivational prefixes and 47 derivational suffixes. The suffix “-ly” is the most dominantly used in the Webtoon. This study revealed not only the detailed morphological process of affix analysis but also the grammatical categories of words and meanings.